The effects of resveratrol treatment on caveolin-3 expression and Na+/K+ ATPase activity in rats with isoproterenol-induced myocardial injury - YEGEN, BERRAK; AKKİPRİK, MUSTAFA; ÖZKAN YENAL, NAZİYE; ÇETİNEL, ŞULE; TETİK, ŞERMİN (KARE PUBL, 2020)
OBJECTIVE: The present study aims to investigate the therapeutic effects of resveratrol (RES) on isoproterenol (ISO) induced myocardial injury rat model. METHODS: Catecholamine-induced heart damage was induced by ISO treatment for 30 days. The rats were divided into four groups as follows: the control group received saline, the ISO group received 5.0 mg/kg ISO, the RES group received 10 mg/kg RES, and the ISO-RES group received 10 mg/kg RES and 5 mg/kg ISO treatments for 30 days. Following echocardiographic measurements and body weight recorded, the rats were decapitated. Plasma and cardiac tissue samples obtained by decapitation were analyzed using biochemical, histopathological, molecular and immunohistochemical methods. RESULTS: In the ISO group, Na+/K+ ATPase activity and ATP content, GSH, and caveolin-3 levels were low. LDH, CK and lysosomal enzyme activities, MDA level, and MPO activity were found to be high. It was determined that GSH and MDA levels and MPO, Na+/K+ ATPase activity, ATP content caveolin-3 levels changes that arose from ISO treatment were suppressed by RES treatment. CONCLUSION: RES treatment has ameliorated all the functional and biochemical parameters. The results obtained in this study suggest that RES is a promising supplement against catecholamine exposure as it improves antioxidant defense mechanisms in the heart. In the light of above-mentioned data, RES can be assumed as a promising agent in ameliorating the oxidative injury of the myocardium.
Keywords: Caveolin-3; heart failure; isoproterenol; lysosomal enzymes; resveratrol; INDUCED CARDIOTOXICITY; HEART; ACID; INFARCTION; PROTECTS; NECROSIS; MYELOPEROXIDASE; MECHANISMS